ULUMUL QUR'AN: CLASSIFICATION OF MAKKIYAH MADANIAH VERSES IN THE QUR'AN - M. Agus Kurniawan; Ahmad Adebisi (Jurnal Ilmiah AZZIQRI: Kajian Keislaman dan Kependidikan, 2022)
Makki Madani in the Ulumul Qur'an is a very important question. The urgency of the situation seen in the Tafseer and Ulumul Qur'an almost all, if not all, make it one of the main topics even the earliest discussed after the meaning of the Qur'an. Although the discussion is simple, not as complicated as the themes of other Qur'anic sciences, in fact it is very urgent to know. Because by knowing it, a commentator or person who studies the Qur'an will be guided by the ability to map out the texts of the abbreviations of verses. Therefore, Makki Madani's insight becomes the basis or starting point for the discussion of nasikh-abrogation, without realizing it, the question of nasikh-mansukh will also be blurred. This is one of the reasons why it became the first theme of the other themes.In these two phases, the Qur'an conducts a dialogue, responds to a messageThe problem is in accordance with the development of the recipient's condition. Since the beginning, the Qur'an has addressed the issue of faith by providing firm and definite provisions for both the Mecca and Medina phases, but on social issues, the Qur'an has dealt with it very differently between the Mecca and Medina periods. The Qur'an addresses these social problems with a gradual approach, that is, responding to them gradually. One of the social problems that were addressed gradually between the Mecca and Medina periods was the issue of khamr